La reingeniería del servicio público: el servicio universal de las telecomunicaciones - Hernández-Mendible, Víctor Rafael (2016)
This paper tries to explain how the regulation of the telecommunications’ activity abandoned the traditional system of State’s public service and evolved to the establishment of a new legal framework that encourages competition among all the economic agents operating in the sector, who must provide all telecommunications services, and, in case that delivery of basic services to all users cannot be done within the framework of the competition, then exceptionally the State as guarantor must impose obligations to ensure the user’s satisfaction in their communication needs.